ORGANIZATIONAL LEARNING IN THE INFORMATION UNITS: from focal group to community of practice - Duarte, Emeide Nóbrega; Araújo da Silva, Alzira Karla; Santos, Edilene Toscano Galdino dos; Lima, Izabel França de; Rodrigues, Marcos Paulo Farias; Costa, Suzana Queiroga da (Perspectivas em Ciência da Informação, 2008)
This work presents the results of the mapping of some practices applied to promote organizational learning. It records the possibility to originate the process of learning from experiences of its own and of others when the focal group technique is adopted as to facilitate the formation of “communities of practice” .It is characterized as a multiple case study in information units, based on interviews and observation of librarians. It was concluded that experiences shared can build collective learning knowledge and identity.